Ground sculpting to enhance energy yield of vertical bifacial solar farms. (1st May 2019) - Khan, M. Ryyan; Sakr, Enas; Sun, Xingshu; Bermel, Peter; Alam, Muhammad A.
Graphical abstract: Highlights: A novel vertical bifacial (vBF) panel array elevated over patterned/sculpted ground. A generalized view-factor model developed to analyze the new solar farm configuration. A ground sculpted vertical bifacial farm (GvBF) yields significantly more energy compared to a monofacial solar farm. This is fundamentally new, economically viable design option for bifacial solar farm design. Abstract: The prospect of additional energy yield and improved reliability have increased commercial interest in bifacial solar modules. Recent publications have quantified the bifacial gain for several configurations. For example, a standalone, optimally-tilted bifacial panel placed over a flat ground (with 50% albedo) is expected to produce a bifacial energy gain of 30% (per module area). In contrast, self and mutual shading in a farm with periodically spaced panels reduces the bifacial gain to 10–15% (per farm area). Bifacial gain is negligible for vertical arrays—although the configuration is of significant interest since it can prevent soiling. Here, we calculate the bifacial gain of a solar farm where vertical arrays are placed over sculpted/patterned ground. We conclude that vertical panels straddling (upward) triangle-shaped ground maximizes the energy output. Our worldwide calculation with up-triangle ground configuration and 50% albedo leads to the following conclusion. Compared to a traditional tilted monofacial design, the bifacial gain is (i) small up to 20° latitude, (ii) increases to 50% at 40° latitude, and (iii) reaches up to 100% at 60° latitude. Overall, high bifacial gains are observed in many regions particularly those with moderate to low clearness index. The enhanced output, along with reduced soiling loss and lower cleaning cost of the ground sculpted vertical bifacial (GvBF) solar farm could be of significant technological interest, especially in regions such as the Middle East and North Africa (MENA) susceptible to significant soiling losses.